THE PHILOSOPHY OF LIFE AND DEATH, LIGHT AND DARKNESS, IN IRANIAN LITERATURE AND ARCHITECTURE (Journal of Teleological Science, 2023)
Life and death has always been one of the main concerns of every thinking person throughout the history of mankind and all the schools of thought, philosophy and religion have tried to explain the meaning of life and specify its goals, and each of them from a different point of view. These coils have looked into each other. However, it is quite clear and obvious that the definition of life without considering death is absurd and futile. But are the concepts of death and life in opposition to each other? And if so, is life superior and more valuable than death? In order to find the above questions, the research, using the analytical-descriptive method and using library sources, first investigated the dual oppositions in structuralist and foundational thinking, and then tried to reread the concepts of life and death in Iranian literature and its corresponding ones. It means there is light and darkness in Iranian architecture.